The Difference in Lemuru Fish Oil Duration of Administration on Connective Tissue Fibroblast Cell Count in Rheumatoid Arthritis Rat Model - Asyirah Mujahidah Fillah; Rena Normasari; Dwita Aryadina Rachmawati (Faculty of Medicine, University of Jember, 2017)
Rheumatoid arthritis is a joint chronic inflammation process leadingto progressive distruction.Cytokinessecreted from chronic inflammation increases fibroblast cell number that synthesize matrix metalloproteinase. Non steroidal anti inflammation drugs administrated to lighten inflammation symptoms had several side effects that increase the urge to discover an alternative antiinflammation with lower side effect like lemuru fish oil. This true experimental study with randomized post test only control group design aimed to investigate the difference in lemuru fish oil duration of administration on connective tissue fibroblast cell count in rheumatoid arthritis rat model. The One Way Anovatestrevealed that there are at least two group means that are statistically significant different from each other with a p value of 0,004. Post Hoc LSD analysis result indicate a significant difference after21 days duration of administrationcompared to 7 days administration with significance value of 0,038.It can be concluded that there is a significant difference in lemuru fish oil administration after21 days duration.